Assessing the level of lead, cadmium and arsenic among farmers in KADA agricultural area, Kelantan - Kasri, Hazmira Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Heavy metals, particularly cadmium, lead, and arsenic, constitute a significant potential threat to human health. This study was conducted to determine the concentration of lead, cadmium and arsenic in nail samples from farmers at Kemubu Agricultural Development Authority (KADA), Kelantan, Malaysia. Control group of this study was selected from participants working in different environment which are USM Health Campus’s staffs. A total of 35 farmers and 35 USM Health Campus’s staffs participated in this study. The fingernails samples were extracted by using acid digestion and then analysed by Atomic Absorption spectrometry (AAS). Checklist was given to participants to get demographic, health status, and their agricultural activities data. In this study, the concentration of heavy metals was within the normal range and varies according to demographic factors. The result showed that the concentration of all heavy metals were significant different in exposed group as compared to control group (p < 0.05). There were also significant correlations between age with concentration of lead, arsenic (r = 0.317 and r = 0.326, resp., p < 0.01) respectively and cadmium (r = 0.257, p < 0.05). Findings suggested that agricultural activities could contribute to the accumulation of heavy metals in farmers. Hence, the control of human exposure to these metals was important in order to prevent adverse health effects. In conclusion, lead, cadmium and arsenic concentration among farmers were lower compared to the allowable limit and they should conduct good agricultural practice to maintain in normal range.